2012
DOI: 10.1371/journal.pone.0045778
|View full text |Cite
|
Sign up to set email alerts
|

Reverting Antibiotic Tolerance of Pseudomonas aeruginosa PAO1 Persister Cells by (Z)-4-bromo-5-(bromomethylene)-3-methylfuran-2(5H)-one

Abstract: BackgroundBacteria are well known to form dormant persister cells that are tolerant to most antibiotics. Such intrinsic tolerance also facilitates the development of multidrug resistance through acquired mechanisms. Thus persister cells are a promising target for developing more effective methods to control chronic infections and help prevent the development of multidrug-resistant bacteria. However, control of persister cells is still an unmet challenge.Methodology/Principal FindingsWe show in this report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…Persister cells were isolated through SOS response selection upon exposure to ciprofloxacin. The use of ciprofloxacin or ampicillin is the main standardized procedure for persister cell isolation and has been widely used in previous studies (2,4,14,19,29,30,44). To ensure adequate isolation of persister cell populations from P. aeruginosa biofilms, we used E. coli cultures as a control, where persister cell isolation from both planktonic and biofilm populations is well documented (2,4,14,19,29,30,44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Persister cells were isolated through SOS response selection upon exposure to ciprofloxacin. The use of ciprofloxacin or ampicillin is the main standardized procedure for persister cell isolation and has been widely used in previous studies (2,4,14,19,29,30,44). To ensure adequate isolation of persister cell populations from P. aeruginosa biofilms, we used E. coli cultures as a control, where persister cell isolation from both planktonic and biofilm populations is well documented (2,4,14,19,29,30,44).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the addition of the quorum sensing inhibitor (Z)-4-bromo-5-(bromomethylene)-3-methylfuran-2(5H)-one (BF8) to Pseudomonas aeruginosa persister cells has been shown to sensitize them to ciprofloxacin and tobramycin, with the effect hypothesized to be the result of changes in the cells' metabolism (19).…”
mentioning
confidence: 99%
“…Treatment of isolated persister cells. Persister cells were isolated as described previously, with minor modifications (57). Stationary-phase cells were treated with ofloxacin (10 g/ml) for 5 h. Higher ofloxacin concentrations or increased incubation times did not lead to a further reduction of the number of surviving cells (data not shown).…”
Section: Methodsmentioning
confidence: 98%
“…However, the mechanism was not determined. Also, Pan et al (53) found a new use for brominated furanones that have been studied for inhibiting quorum sensing by finding that (Z)-4-bromo-5-(bromomethylene)-3-methylfuran-2(5H)-one wakes P. aeruginosa planktonic and biofilm persister cells. They also determined that the compound is effective with mucoid P. aeruginosa (54).…”
Section: Preventing Persistence and Waking Persistersmentioning
confidence: 99%